Walt Whitman : words for America - Kerley, Barbara (Scholastic Press, 2004)
A biography of the American poet whose compassion led him to nurse soldiers during the Civil War, to give voice to the nation's grief at Lincoln's assassination, and to capture the true American spirit in verse.